New species and first records of Macunahyphes Dias, Salles & Molineri, 2005 (Ephemeroptera: Leptohyphidae) from Bahia state, Brazil - Almeida, Everlin; Mariano, Rodolfo (Zootaxa, 2015)
A new species of Macunahyphes Dias, Salles & Molineri (Leptohyphidae) is described based on male imagos collected in the Michelin Ecological Reserve, Igrapiúna, Bahia state, Brazil, located in a preserved area of Atlantic Forest. The male of the new species can be distinguished from all congeners by the shape of the penes, which have a pair of unusual spines, and are elongated with lateral hook-shaped projections distributed from the base to the middle region. This new species represents the first record for the genus from Bahia State.